Motivasi Belajar Mahasiswa Program Studi Rekam Medis Pasca Pandemi - Sevilla, Flavia; Rumana, Nanda Aula; Sonia, Dina; Putra, Daniel Happy (Lembaga Penerbitan Universitas Esa Unggul, 2024)
AbstractMotivation is a movement within a person, one of which is learning. High motivation will create good results, too. This research aims to determine the description of learning motivation in students of the Medical Records and Health Information study program at Esa Unggul University in the post-pandemic period through six indicators, namely intrinsic, extrinsic, task value, learning control, self-efficacy, and anxiety. This research uses a descriptive method with a quantitative approach. The research sample consisted of 82 students from three different classes. The results of this research show that based on intrinsic indicators 75.2%, extrinsic 81.4%, task value 76.5%, learning control 76.5%, self-efficacy 80.3%, and anxiety 73.4%), the results obtained that post-pandemic medical records students' learning motivation was 51.2% high motivation and 48.8% low motivation.Keyword: medical record students, learning motivation, MSLQ AbstrakMotivasi merupakan gerakan dalam diri seseorang salah satunya dalam belajar. Motivasi yang tinggi akan menciptakan hasil yang baik juga. Tujuan penelitian ini untuk mengetahui gambaran motivasi belajar pada mahasiswa Rekam Medis dan Informasi Kesehatan Universitas Esa Unggul di pasca pandemi melalui enam indikator yakni intrinsik, ekstrinsik, nilai tugas, pengendalian pembelajaran, efikasi diri, dan kecemasan. Penelitian ini memakai metode deskriptif kuantitatif. Sampel penelitian ini berjumlah 82 mahasiswa dengan tiga angkatan berbeda. Hasil penelitian ini menunjukkan berdasarkan indikator intrinsik 75,2%, ekstrinsik 81,4%, nilai tugas 76,5%, pengendalian pembelajaran 76,5%, efikasi diri 80,3%, dan kecemasan 73,4%, sehingga didapatkan hasil bahwa motivasi belajar mahasiswa rekam medis di pasca pandemi 51,2% motivasi tinggi dan 48,8% motivasi rendah.Kata Kunci: mahasiswa rekam medis, motivasi belajar, MSLQ